Brain and Symmetry – A Principle Theory of Brain Function - Stueber, Juergen J. (Journal of NeuroPhilosophy, 2026)
The “Triggering Brain” hypothesis (Stueber, 2023) proposes brain function as a relational process based on biological equilibrium rather than absolute signal values. The present essay extends this model into a broader principle theory developed across physics, evolution, physiology, and the brain. In physics, symmetry, invariance, and relativity are examined as principles of stable order. In evolution, bilateral body plans and paired sensory systems are interpreted as selective pressures for relational neural processing. In physiology, homeostasis is reconsidered as a systemic principle in the sense of Bernard and Cannon rather than as a collection of local compensatory mechanisms. Within this framework, synchrony within the brain is proposed as the neurophysiological correlate of both biological equilibrium and invariance. “Triggering” is understood not as an occasional event, but as the fundamental mode of neural operation. The Kuramoto model provides a framework for interpreting EEG data in terms of phase coherence rather than signal amplitude. Several avenues for empirical falsification are proposed using EEG, MEG, and individualized anatomy-guided electrode placement (the “sulcal-fingerprint”). The hypothesis is presented as a principle theory in the sense of Albert Einstein and evaluated in light of Karl Popper’s criterion of falsifiability. Rather than competing with existing neuroscience, the hypothesis proposes synchrony as the biological state underlying stable neural function. Provided that this hypothesis is justified, identifying and measuring the biological “invariant” may significantly improve neurological diagnostics and therapeutic intervention.